The new solution selling : the revolutionary sales process that is changing the way people sell - Eades, Keith M. (McGraw-Hill, 2004)
This work covers solution selling principles, creating new opportunities, what to do when you're not first, how to qualify, control, and close, and managing for a high performance sales culture. It also includes sales architecture and framework.